Mapping Language in the Discourse of Intimacy and Sexuality for Autistic People: A Teun van Dijk Critical Discourse Analysis - Siroj, Muhammad Badrus (Jurnal Sastra Indonesia, 2023)
People with Autism Spectrum Disorder (ASD) have basic difficulties in language and communication. Despite that, they have a desire to feel and share emotions like love and sex. The purpose of this study is to describe how the linguistic construction of an autistic person’s language by others affects their talk of love and sex. These structures include the form and construction of discourse as realized in their utterance (their ‘verbal behavior’). This research adopts a qualitative interpretative methodology by Critical Discourse Analysis (CDA). Data were collected from documents, observations, and in-depth interviews, and analyzed with van Dijk’s CDA model to identify discourse strategies through textual, social cognition, and social context patterns of analysis. The kinds of discourse about affection and sex discourse constructed by autistic people are talk used within social interaction, talk for social communication, as well as symbolic-imaginary play. Linguistic realizations found are direct and simple expressions, wishing for closeness, respect for others, and preference marking behaviors. With the characteristics of autistic people preferring clear, direct language, having limited or absent understanding of social context, no emotional expression in sexual behavior, but sensitivities to physical changes, and an absence of awareness around rights and personal boundaries, this discourse is formed. The aim is that, by gaining an understanding of the discourse constructions present in the lives of autistic participants, society will become more accepting and caring of their comfort and emotional well-being around love and sex.